One Planet Is Enough Tackling Climate Change and Environmental Threats through Technology - Westergård, Rune (Springer International Publishing, 2018)
The present book offers a compelling sketch of how technological advances have shaped humankind's evolution and how they can unlock ways to combat climate change and environmental threats. It also reveals new perspectives on climate change and sustainable development by harnessing technology. Given today's conditions, only a homeless vegan could achieve a sustainable ecological footprint. In reality, it would be impossible, and even destructive, to attempt to save the planet by discontinuing consumption. It would disrupt evolution and threaten the driving forces of the technology that is our hope for combating climate change and environmental threats in the future. This is the opinion of Rune Westergård, engineer, entrepreneur, and environmental debater, with several decades of experience from the field of environmental and energy technology. He challenges many established truths on consumption and sustainability and demonstrates how and why they are flawed. From his point of view, both continued global growth and increased welfare are entirely possible within the ecological limitations of our planet. Once we learn to put technology to our best advantage, one planet will be enough.